2006
DOI: 10.1111/j.1398-9995.2006.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear relations between house dust mite allergen levels and mite sensitization in farm and nonfarm children

Abstract: Our data suggest a bell-shaped dose-response relationship between mite allergen exposure and sensitization to mite allergens. In populations with high microbial agent levels and low sensitization rates, the curve is shifted down.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 30 publications
8
37
0
Order By: Relevance
“…A significant, non-linear relationship between endotoxin exposure and a number of common allergens was seen in adult pig farmers as the risk of sensitization was strongly decreased with increasing exposure to endotoxin [39]. Schram-Bijkerk et al [40] observed similar findings in house dust mites and mite sensitization in farming and non-farming children. Interestingly, exposure to high levels of crude sources of β-glucans was observed to be associated with decreased risk for recurrent wheezing among infants [41,42], indicating that β-glucan exposure may protect against asthma development.…”
Section: Resultssupporting
confidence: 65%
“…A significant, non-linear relationship between endotoxin exposure and a number of common allergens was seen in adult pig farmers as the risk of sensitization was strongly decreased with increasing exposure to endotoxin [39]. Schram-Bijkerk et al [40] observed similar findings in house dust mites and mite sensitization in farming and non-farming children. Interestingly, exposure to high levels of crude sources of β-glucans was observed to be associated with decreased risk for recurrent wheezing among infants [41,42], indicating that β-glucan exposure may protect against asthma development.…”
Section: Resultssupporting
confidence: 65%
“…Based on the recent observation of very high concentrations of allergens on farms [148], the hypothesis of tolerance induction by antigen exposure in early life [44] has been raised to explain the protective effect of farming environment. However, the only study that objectively assessed allergen concentrations at home did not find any significant association with allergic sensitisation [42]. As a consequence, because of a lack of data, the hypothesis of immune tolerance induction is controversial, and further studies are needed in order to replicate previous results and to better understand how biological exposure might interact with the immune system [149].…”
Section: In Childrenmentioning
confidence: 73%
“…We will not detail these results in this section as several recent reviews have discussed this subject [40,41]. However, we would like to underline recent results, which suggest a nonlinear relationship between exposure to allergens and allergic diseases [42,43]: high exposure to HDM allergens might be protective against the risks of asthma and allergic sensitisation. This has been suggested by the ''high-dose tolerance'' hypothesis put forward for exposure to the cat allergen [44].…”
Section: Biological Pollutantsmentioning
confidence: 89%
“…For example, there is some controversy on the possibility of identifying meaningful threshold levels of exposure (Custovic and Chapman, 1998). Also, although the dose-response relationship between HDM allergen exposure and sensitisation is generally believed to be linear, some studies suggest that it could be bell-shaped in some circumstances (Schram-Bijkerk et al 2006).…”
Section: Scenarios Modelling Resultsmentioning
confidence: 99%